INFLUENCE OF MOTOR MODES ON INDICATORS OF PHYSICAL FITNESS OF JUNIOR SCHOOLCHILDREN - Kondakov, V.L.; Voloshina, L.N.; Kopeikina, E.N.; Kadutskaya, L.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the effectiveness of motor modes of younger schoolchildren and their influence on the optimization of motor activity and the level of physical fitness of children aged 9-10 years. Methods and structure of the study. The experiment involved students of secondary schools in Belgorod (n=60, 32 girls, 28 boys aged 9-10 years). Scientific work was carried out from September 2021 to May 2022. The students of the experimental group attend a full-time school with a variable system of physical education, and the students of the control group attend a school with a traditional model of organizing the educational process. Results and conclusions. As a result of the analysis of the correlation dependence of the studied indicators, it was revealed that the weakest correlation is observed between the indicators of the volume of motor activity and the results of running 1000 meters in all the studied children aged 9-10 years. The revealed data, according to the authors, are due to the age-related features of the development of endurance, as well as the insufficient attention of teachers to the development of this physical quality in classroom and extracurricular physical education classes with primary school students.